Pengenalan Data Scientist Pada Peserta PKBM AL HABIB Melalui Belajar Dasar Coding Python - Arjon Sitio; Anita Sindar; Murni Marbun; Dinda Tiara; Aswin Aswin (Universitas Mathla'ul Anwar Banten, 2022)
Data scientist is a profession that is claimed to be excellent in the 21st century by many experts from big companies in the world. The area of competence that really needs to be mastered by job seekers other than office computers is Data Scientist skills. For the younger generation, talking about Data Scientist is related to programming or coding. Things that have never been done at PKBM Al Habib. With the service program from the STMIK Pelita Nusantara in collaboration with PKBM Al Habib, Introduction of Data Scientist was carried out for PKBM Al Habib Participants through Basic Python Coding Learning. The purpose of the activity is to introduce Data Scientists to members of the Al Habib PKBM training or course so as to produce Data Scientists through learning basic python coding. The achievement of this training is that participants are able to recognize and master the basics of Python programming.